2005
DOI: 10.1159/000085144
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Debriefing and Modifications to Cognitive Behavior Therapy for Posttraumatic Stress Disorder

Abstract: Background: Psychological debriefing uses brief unsystematic exposure, and is ineffective for posttraumatic stress symptoms and disorder. Systematic exposure alone and cognitive restructuring alone are each effective. Other approaches too may be useful. Methods: The treatment of 3 posttraumatic stress disorder (PTSD) patients is detailed in which there was no exposure to the main traumatic event.There was exposure to related cues in case 1, exposure to related and other cues followed by well-being therapy (WBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 81 publications
1
29
0
1
Order By: Relevance
“…Future research should implement more sophisticated, and probably longer programs, and perhaps combine them with antidepressant for the patients resistant to treatment. In chronic PTSD, new therapies based upon positive psychology could be of value and deserve controlled trials [14]. Improvement of the training of the therapists to deal with chronic patients could also be a key issue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should implement more sophisticated, and probably longer programs, and perhaps combine them with antidepressant for the patients resistant to treatment. In chronic PTSD, new therapies based upon positive psychology could be of value and deserve controlled trials [14]. Improvement of the training of the therapists to deal with chronic patients could also be a key issue.…”
Section: Resultsmentioning
confidence: 99%
“…These questions are dealt with by humanistic approaches, as Rogerian therapy, or methods related to the positive psychology current, which are centered on personal growth. An uncontrolled study reported some positive and long-lasting effects of well-being therapy in 3 patients [14]. In that study, the model of Ryff and Singer [15] was used in 2 patients and exposure unrelated to the central traumatic event (irrelevant exposure) in one.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps most notably, SWT does not include the conventional exposure procedures that often make therapy an emotionally demanding endeavor. While the emotional costs of treatment are not likely to outweigh its benefits (interestingly, also for therapists [44]), it is tempting to contemplate the possibility of circumventing conventional imaginal exposure [45]. Perhaps SWT allows greater control of the intensity of negative emotions during imaginal exposure, resulting in (nondissociative) anxiety levels that are optimal for emotional processing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is known that psychological debriefing after traumatic events, where victims are encouraged to expose themselves to specific traumatic cues, is ineffective. It is even hypothesised that this method may increase awareness of distress and aggravate systems by sensitising victims to these experiences [31]. Marlatt [32] also warns about a ‘paradoxical increased sensitisation effect’ as a result of CET after the drug user experiences a first lapse.…”
Section: Discussionmentioning
confidence: 99%